(3MOhO GdQbGHI GdbVGFjI Ydi SdWI GdEOGQI GdJbOjQjI (B: s (3OQGSI ebGQfI (B/ s - (3NGdO SjO eMeO eMehO MeGOs; (3LGHQ LGO fUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3JfGhdJ gPg GdOQGSI GdHMK aj SdWI GdJbOjQ GdEOGQi GdebQQI ddEOGQI h GdeUWdM Ydi JSejJgG HSdWI GdEOGQI GdJbOjQjI (B: (3ceG JfGhdJ HjGf eOj QbGHI GdbVGA YdjgG (B: (3OQGSI GdSdWI GdJbOjQjI ddEOGQI HHjGf JYQjagG h YdGbJgG HeHOC GdeTQhYjI h JejjRgG Yf GdGNJUGU GdebjO h HjGf eQGMd XghQgG h eHQQGJgG h ehba GdTQjYI GdGSdGejI efgG Ke HjGf eLGd gPg GdSdWI GdfXQj h GdYedi h HjGf YdGbJgG HGdbQGQ GdSdHj h cPdc HjGf YdGbJgG HfXQjJj CYeGd GdSjGOI h GdXQha GdGSJKfGFjI h GNJJe acQI GSJfaGO GdEOGQI dSdWJgG GdJbOjQjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2011s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B833-885s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdQbGHI GdbVGFjIs; (3GdSdWI GdJbOjQjI ddEOGQIs; (3eHOC GdeTQhYjIs; (3eLGdGJ GdSdWI GdJbOjQjI s; (3GdGNJUGU s; (3GdZGdjI GdTcds; (3GdhXjaI GdYGeI s; (3GdSdWI GdEOGQjIs; (3QbGHI GdNWC GdHjf s; (3QbGHI GdehGRfI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes